Sociological implications of faith-healing and herbal-therapy applications in Christ Apostolic Church - Adekoya, Samuel Olamide; Oyebanji , Israel Temitope; George Olatayo; Afolorunsho , Olalekan Dairo (Corpus Intellectual, 2024)
Christ Apostolic Church is believed to have a strong belief in faith healing. This is evidently rooted in the tenets of the church and its origin is linked to the famous Precious Stone Society, a prayer group that started in Southern Nigeria in 1918. Christ Apostolic Church is one of the most influential Pentecostal organizations in Nigeria. This paper defined the church's tenet of faith regarding faith-healing, it also discussed the sociological implication of herbal therapy application in Christ Apostolic Church. A combination of theological, historical, and phenomenological approaches are used. The results show that CAC believed in the Faith-Healing for believers which is the centre of Pentecostal theology. Also, research reveals that some of the members of Christ Apostolic Church believed that Herbal Therapy can also be considered in as much as they would not negatively influence one’s spiritual life and cause any other havoc to the Christian community.